Bifunctional conjugates with potent inhibitory activity towards cyclooxygenase and histone deacetylase. Issue 3 (1st February 2017) - Raji, Idris; Yadudu, Fatima; Janeira, Emily; Fathi, Shaghayegh; Szymczak, Lindsey; Kornacki, James Richard; Komatsu, Kensei; Li, Jian-Dong; Mrksich, Milan; Oyelere, Adegboyega K.
Graphical abstract: Abstract: We herein disclose a series of compounds with potent inhibitory activities towards histone deacetylases (HDAC) and cyclooxygenases (COX). These compounds potently inhibited the growth of cancer cell lines consistent with their anti-COX and anti-HDAC activities. While compound2b showed comparable level of COX-2 selectivity as celecoxib, compound11b outperformed indomethacin in terms of selectivity towards COX-2 relative to COX-1. An important observation with our lead compounds (2b, 8, 11b, and17b ) is their enhanced cytotoxicity towards androgen dependent prostate cancer cell line (LNCaP) relative to androgen independent prostate cancer cell line (DU-145). Interestingly, compounds2b and17b arrested the cell cycle progression of LNCaP in the S-phase, while compound8 showed a G0/G1 arrest, similar to SAHA. Relative to SAHA, these compounds displayed tumor-selective cytotoxicity as they have low anti-proliferative activity towards healthy cells (VERO); an attribute that makes them attractive candidates for drug development.